Influx of illegal immigrants: a study on the law Governing immigration officers / Muhamad Jazli Azman, Norsyakiratul Jannah Sobani and Nurfatihah Ammad @ Ahmad - Azman, Muhamad Jazli; Sobani, Norsyakiratul Jannah; Ammad @ Ahmad, Nurfatihah (Faculty of Law, 2014)
In the early 1970s, Malaysia began to be entered by foreign workers, all of whom were irregular migrants. A decade later their uncontrolled entry left several negative consequences, especially to the internal and border security of the country. To overcome the problems Malaysia introduced many relevant policies as well as increase the punishment towards the illegal immigrants in the Immigration Act. However, it has not been able to curb the expansion of irregular migrants; instead their number has risen in parallel with that of legally recruited ones. Recently, there are many cases involved the integrity of the immigration officers had risen and reported in the local newspaper. This problem had directly affected the number of the illegal immigrants that enter into our country. Thus, this research is an attempt to overcome the integrity problem among the officers and directly it would also overcome the entrance of the illegal immigrants in our country. The research has five chapters. The first contains the introduction and research background which explains the entrance of the illegal immigrants in Malaysia and the law that governed these illegal immigrants. It also contains the objective, problem statement, scope and methodology of research carried out and the limitation of the research that we faced in order to complete this research. The literature review is given in Chapter 2, in which it emphasized about the integrity problem among the immigration officers that lead to the entrance of the illegal immigrants. While chapter 3 describes the lacunae and loophole in the law that governed the officers as well as the illegal immigrants which is Immigration Act 1959. Chapter 4 focuses on the finding that we get through interview irregular migrants who were apprehended and placed in the state run depot prior to deportation. It examines their interface with the Malaysian immigration, labor and criminal laws and how policy measures put in place impacted on their lives and work.